FATORES CRÍTICOS DE SUCESSO NO USO DE EARNED VALUE MANAGEMENT EM PROJETOS DE DESENVOLVIMENTO DE SOFTWARE E A RELAÇÃO COM A QUALIDADE PERCEBIDA - Lacerda, Isac Mendes (2009)
The objective of this study is to identify Critical Success Factors (CSF) in the use of Earned Value Management (EVM), as a monitoring and control technique, in software development projects and identify possible influence of the technique in the perception of the quality in relation to project management between the involved. The work uses as a referential theory Rockart s (1979) method of CSF, the prognostics of Product Life Cycle (PLC) by Porter (1986), the monitoring technique and project control EVM, the SERVQUAL instrument by Parasuraman et al. (1985) and software development process models (prescriptive and agile). The methodology uses as a base the hypothetical-deductive method of Popper (1975) which assumes from gaps or ruptures in existing theories the elaboration of verifiable hypotheses. After testing the hypotheses of a study it is possible to corroborate or refute them, which means the confirmation of the conjectures or the elimination of false beliefs. With this approach, seven potential critical success factors were elaborated, in the use of EVM for software projects, based on the prognostics of the PLC introduction phase by Porter (components of the first hypothesis research). There were also elaborated, based on the SERVQUAL, six potential positive influences in which EVM could cause in the perception of quality regarding to project management between those involved (components of the second hypothesis research). The elements that compose the first and second hypotheses were tested through a field questionnaire applied on three multinational companies of Brazilian origin, that develop software, and are active in the state of Rio de Janeiro. The data collected were dealt with through the Kolmogorov- Smirnov method and Paraconsistent Logic. Of the seven extracted factors of PLC by Porter, six were validated as indeed critical. In the case of the six influences that EVM can cause, extracted of the instrument SERVQUAL, four were considered true and the others two were considered true with tendency to the inconsistency, according to the applied method (Paraconsistent Logic). This way, the conclusion of the work could assist companies which conduct software development projects interested in the employment of a monitoring and control technique.